Chronic Toxic Hepatitis and Features of Structural Changes in the Small Intestinal Mucosa (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The article presents literature data on the study of the effect of chronic toxic hepatitis on the structural and functional features of the small intestine of rats, and considers the prospects for further research in this direction.